Bullying: representações sociais de professores de uma escola pública - Letícia Martins Arruda; Joyce Karolina Ramos de Oliveira Silva; Ester Mascarenhas Oliveira; Flávia Carvalho Malta de Mello; Aglais Vieira da Silva; Julliane Messias Cordeiro Sampaio (Universidade de Pernambuco, 2021)
Objective: to learn the social representations of teachers about bullying. Method: This was a descriptive study with a qualitative approach, based on the Theory of Social Representations, carried out with 10 teachers interviewed from the 6th and 7th grades of a public school in the Federal District. Results: the teachers admitted that this phenomenon is broad, complex and that it occurs regularly in schools. Final Considerations: It was noted that there is still a lack of knowledge by teachers on this subject, as only three of them emerged knowledge about the manifestations of bullying but, almost unanimously, pointed out that they are not prepared to resolve this type of conflict given the multifaceted characteristic of the phenomenon.